Integration into a PhD Program: An Arts-Based Research Approach to Examine the Experiences of Doctoral Students - Yılmazlı Trout, İnci (Acta Paedagogica Vilnensia, 2018)
[full article in English] This article explores the experiences of twelve doctoral students during their processes of integrating into a doctoral program. In this qualitative study, by using a participatory, arts-based research design, twelve participants were asked to create collages and write narratives depicting their collages representative of their integration experiences. The research question this study addressed is the following: how have the students experienced integrating into their doctoral program? The gathered data revealed that academic and social factors play important roles in shaping and impacting the doctoral journey of a student.